HUBUNGAN ANTARA PENYESUAIAN PERKAWINAN DENGAN KEHARMONISAN KELUARGA PADA AWAL PERKAWINAN PASANGAN BERSTATUS MAHASISWA - Rachmawati, Susi (TALENTA, 2014)
Once  the  importance  of  family  harmony  for  the  development  of  the  younger generation  of  the  child  as  a  member  of  the  family,  so  expect  every  couple  to  seek  the harmony and harmony in the family. The population in this study were all female students who have been married at UMS in 9 subjects the faculty of Health Sciences, Faculty of Psychology  13  subjects,  FKIP  11  subjects,  3  subjects  Faculty  of  Law,  Faculty  of Economics  4  subjects,  all  of  which  amounts  to  40  subjects.  The  sampling  technique population studies.  Measuring tool used to reveal the research variables there are two kinds of measuring instruments, namely: (1) the scale of family harmony, and (2) marital adjustment scale. Analysis of the data in this study using product moment correlation.Based  on  the  analysis  of  the  obtained  highly  significant  correlation  between marital adjustment with family harmony or rxy of 0.439 with p <0.01, which means there is a very significant positive correlation between marital adjustment to family harmony. The better the  adjustment of individual marriage, the higher the harmony of the family, and  vice  versa.  Mean  empirical  marital  adjustment  variable  with  a  mean  of  123.750 hypothetical  average  of  105.  So  the  empirical>  hypothetical  average  which  means generally the subject  of a student partner marital adjustment in the categorization UMS high, while empirical variables family harmony at 137.425 with a hypothetical average of 110. So the empirical mean > hypothetical average which means generally the subject has a high family harmony. The role of marital adjustment to the harmony of the family (SE) of 19.3%. It was concluded that there was a significant positive correlation between marital adjustment to family harmony.Keywords: Redefining marriage, family harmony